Kebebasan Berpendapat dalam Perspektif Hukum Indonesia di Era Digital: Jaminan Konstitusional, Pembatasan yang Sah, dan Arah Reformasi Regulasi - Indrasatya Octavianus Nasirun; Yolanda Salainti; Hendrasari B. Rawung; Lutfia Harimu; Ridho Pakaya (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Freedom of opinion is an essential constitutional right for democratic accountability, citizen participation, and the exchange of ideas in digital public spaces. This right is guaranteed by the 1945 Constitution and various international human rights instruments that Indonesia has ratified. However, the expansion of social media, disinformation, hate speech, doxing, cyberharassment, and inconsistent law enforcement have made its protections even more complex. Tensions arise between the need to maintain order and protect the dignity of individuals on the one hand, and the state's obligation not to silence legitimate expressions on the other. This article examines the legal position of freedom of opinion in Indonesia, the validity of its restrictions in the digital environment, and the direction of reform after the amendment of the Electronic Information and Transaction Law (UU ITE) in 2024 and the latest Constitutional Court ruling. Using normative juridical methods through legislative, conceptual, case, and comparative approaches, this study analyzes how positive legal norms are applied in practice and how arrangements in other countries can be referenced. The results of the study show that multi-interpreted articles have the potential to cause excessive criminalization and a chilling effect on freedom of expression. Therefore, this article emphasizes the need to shift from a multi-interpretive and punitive model to a governance based on rights, proportionality, and transparency, so that the protection of freedom of opinion can run in balance with the protection of the rights of other citizens in the digital era.